Jigsaw Type of Cooperative Learning as a Means of Improving High School-Studentsâ Mathematical Communication Ability - Ahmad, Ahmad; Jazuli, Akhmad (EDUCARE, 2009)
ABSTRACT: The mathematical communication is the basic ability which must be possessed by mathematics practitioners and users during teaching-learning process and assessing mathematics. By using Jigsaw technique as a part of cooperative learning, this technique considers students to work interdependently in a group of four to six but at the same time have individual responsibility. Every group is responsible for the mastery of the learning material. The aim of this research, however, was to examine the quality of mathematical communication ability between students who were treated with cooperative learning model and those with conventional model. The population of this study were second grade students of SMUN Banyumas in the academic year 2005/2006. Two classes were taken as sample, each of them had thirty students. Data were collected by means of communication ability test that had satistactory face and content validity and had reliability of 0.5335 (high reliability). Based on analisys result using t-test, it was concluded that the cooperative learning model gave better result to the students communication ability than the conventional one.KEY WORDS: jigsaw, cooperative learning model, conventional learning model, mathematical communication ability.Â Â About the Authors: Drs. Ahmad, M.Pd. and Drs. H. Akhmad Jazuli, M.Si. are Lecturers at the Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto) in Central Java, Indonesia. They can be reached at: ahmadump@yahoo.co.id and jazuli_akhmad@yahoo.comHow to cite this article? Ahmad & Akhmad Jazuli. (2009). âJigsaw Type of Cooperative Learning as a Means of Improving High School-Studentsâ Mathematical Communication Abilityâ in EDUCARE: International Journal for Educational Studies, Vol.1(2) February, pp.207-218. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 3, 2008); Revised (January 15, 2009); and Published (February 17, 2009).